अनुसन्धानमा शोध अन्तराल - Acharya, Baburam (Haimaprabha, 2026)
The present article is related to the concept of Literature Review and research gap in the context of research articles. In the article prepared on the basis of using the prevailing framework in the field of research, it is factual, specific and academic as it seeks to solve the academic problem. As in large-scale research at the above level, the review of previous work and the identification of research gaps are the main basis for research that will be presented in a small scale with a short period of time. It is important and challenging to correctly identify research gaps in research work. The presented study is focused on the purpose of finding the basis for identifying the concept of research gap. This article is based on qualitative research, which is a factual analysis of the subject using material collected from library-related work. Although all structural elements are equally important in the article, since the study of previous work and the search for research gaps are done at the initial stage, there is no binding recognition that must be kept as subtitles or words. But in the changed context, it is concluded that it is timely to indicate the research gap with a brief description of the Literature Review, not only at the research level of the academic level, but also in the research article.